The Roles of School Leadership and Teachers in Empowering Female Students’ Education in Rural Southern Part of Azerbaijan - Abbasova, Lamiya; Zahidzada, Aida; Mirzaliyeva, Khatira (My University, 2026)
Empowering female students’ education is vital for the development of female’s education in the southern regions of Azerbaijan. Thus, perceiving the female students’ education can further lead to professional growth, and the overall high quality of education in southern regions, including Lerik, Lankaran, and Jalilabad. Since female students’ educational outcomes are not appealing enough in the mentioned regions, we decided to explore the factors that prevent female students’ education. In this study, semi-structured interviews were conducted in three schools with a total of 15 participants, 3 principals and 12 teachers, respectively. The interviews were either face-to-face or online. The results indicate that family-oriented and social factors, financial and geographical challenges, early marriage, shortage of teachers, and poor school conditions are the primary barriers that affect female students’ poor participation and motivation to education. Implementing strategies by school principals and teachers, such as raising parental awareness about the issue, presenting educated women as role models to students, elaborating school-based activities among head teachers, ensuring financial aid and institutional support can contribute to female students’ education in southern regions of Azerbaijan. At the end, as a final product, we suggest to conduct workshops in these schools that aim to raise parental awareness and shift their mindset about education that addresses the importance of female students’ education and promoting equal opportunities for them.
Keywords: School Leaders and Teachers; Empowering Female Students’ Education; Southern Regions of Azerbaijan